Proteomic analysis of gemcitabine-resistant pancreatic cancer cells reveals that microtubule-associated protein 2 upregulation associates with taxane treatment - Le Large, Tessa Ya Sung (Ther Adv Med Oncol, 2019)
BACKGROUND: Chemoresistance hampers the treatment of patients suffering from pancreatic ductal adenocarcinoma (PDAC). Here we aimed to evaluate the (phospho)proteome of gemcitabine-sensitive and gemcitabine-resistant PDAC cells to identify novel therapeutic targets and predictive biomarkers. METHODS: The oncogenic capabilities of gemcitabine-sensitive and resistant PDAC cells were evaluated in vitro and in vivo. Cultured cells were analyzed by label-free proteomics. Differential proteins and phosphopeptides were evaluated by gene ontology and for their predictive or prognostic biomarker potential with immunohistochemistry of tissue microarrays. RESULTS: Gemcitabine-resistant cells had increased potential to induce xenograft tumours (p value < 0.001). Differential analyses showed that proteins associated with gemcitabine resistance are correlated with microtubule regulation. Indeed, gemcitabine-resistant cells displayed an increased sensitivity for paclitaxel in vitro (p < 0.001) and nab-paclitaxel had a strong anti-tumour efficacy in vivo. Microtubule-associated protein 2 (MAP2) was found to be highly upregulated (p = 0.002, fold change = 10) and phosphorylated in these resistant cells. Expression of MAP2 was correlated with a poorer overall survival in patients treated with gemcitabine in the palliative (p = 0.037) and adjuvant setting (p = 0.014). CONCLUSIONS: These data show an explanation as to why the combination of gemcitabine with nab-paclitaxel is effective in PDAC patients. The identified gemcitabine-resistance marker, MAP2, emerged as a novel prognostic marker in PDAC patients treated with gemcitabine and warrants further clinical investigation.